Diagnostic Accuracy of Touch Imprint Cytology in Ovarian Neoplasms - Riaz, Aisha; Khalid, Ahmareen; Tanwani, Ashok Kumar (International Journal of Pathology, 2018)
Objective: Ascertain the status of Intraoperative Touch Imprint Cytology as a diagnostic and supportive investigationfor ovarian neoplasms thus facilitating individualized treatment.Study design: Cross sectional studySetting: Department of Pathology, Pakistan Institute of Medical Sciences, IslamabadDuration of study: June 2011 to June 2013Methodology: Touch Imprint smears were made from fresh unfixed ovarian samples received. Imprints were takenand slides were immediately fixed in 95% ethyl alcohol and stained with the haematoxylin and eosin stain. Theresults of Touch Imprint cytology and the results were compared with the final histopathological diagnosis ineach case.Results: The total number of ovarian tumors studied was 60. Age range of the patients was 10 to 70 years. Out of60 cases there were 31 benign lesions, 4 borderline epithelial neoplasms and 25 malignant tumors according to thefinal histopathological diagnosis. The touch imprint results labeled 32 lesions as benign and 28 lesions as malignant.Comparing the histopathology and touch imprint results, 55 out of 60 cases were concordant with sensitivityand specificity of 93% and 83.3% respectively. Characteristic cytological patterns and morphology was observedin various ovarian neoplasms.Conclusion: Touch Imprint cytology can be utilized as an adjunct to histopathology as a quick diagnostic toolwith high diagnostic accuracy.